Factors Influencing the Integrity of Financial Statements in Consumer Goods Companies Listed on the IDX for the 2018-2020 Period - Rizkyka Agusti Fadillah; Rizqy Fadhlina Putri (Journal of Finance and Business Digital, 2023)
This study aims to determine the contribution of audit quality, leverage, profitability and company size to the integrity of financial reports in Consumer Goods Companies listed on the Indonesia Stock Exchange in 2018-2020. The population studied is all Consumer Goods companies on the IDX. Sampling using Purposive Sampling method. which produces a sample of 26 companies. The type of research used is quantitative. The data analysis tools are multiple linear regression analysis, partial test, simultaneous test and test of the coefficient of determination. The result of this research is that audit quality and company size partially do not contribute to the integrity of financial statements and what contributes to the integrity of financial statements are leverage, profitability and company size. Overall audit quality, leverage, profitability and company size contribute to the integrity of financial statements.